Factors associated with complete clip closure after endoscopic mucosal resection of large colorectal polyps - Ortiz, Oswaldo; Rex, Douglas K.; Grimm, Ian S.; Moyer, Matthew T.; Hasan, Muhammad K.; Pleskow, Douglas; Elmunzer, B. Joseph; Khashab, Mouen A.; Sanaei, Omid; Al-Kawas, Firas H.; Gordon, Stuart R.; Mathew, Abraham; Levenick, John M.; Aslanian, Harry R.; Antaki, Fadi; von Renteln, Daniel; Crockett, Seth D.; Rastogi, Amit; Gill, Jeffrey A.; Law, Ryan; Wallace, Michael B.; Elias, Pooja A.; MacKenzie, Todd A.; Pohl, Heiko; Pellisé, Maria (Endoscopy, 2021)
Background and study aim Delayed bleeding is a common adverse event following endoscopic mucosal resection (EMR) of large colorectal polyps. Prophylactic clip closure of the mucosal defect after EMR of nonpedunculated polyps larger than 20 mm reduces the incidence of severe delayed bleeding, especially in proximal polyps. This study aimed to evaluate factors associated with complete prophylactic clip closure of the mucosal defect after EMR of large polyps.Methods This is a post hoc analysis of the CLIP study (NCT01936948). All patients randomized to the clip group were included. Main outcome was complete clip closure of the mucosal resection defect. The defect was considered completely closed when no remaining mucosal defect was visible and clips were less than 1 cm apart. Factors associated with complete closure were evaluated in multivariable analysis.Results In total, 458 patients (age 65, 58 % men) with 494 large polyps were included. Complete clip closure of the resection defect was achieved for 338 polyps (68.4 %); closure was not complete for 156 (31.6 %). Factors associated with complete closure in adjusted analysis were smaller polyp size (odds ratio 1.06 for every millimeter decrease [95 % confidence interval 1.02–1.08]), good access (OR 3.58 [1.94–9.59]), complete submucosal lifting (OR 2.28 [1.36–3.90]), en bloc resection (OR 5.75 [1.48–22.39]), and serrated histology (OR 2.74 [1.35–5.56]).Conclusions Complete clip closure was not achieved for almost one in three resected large nonpedunculated polyps. While stable access and en bloc resection facilitate clip closure, most factors associated with clip closure are not modifiable. This highlights the need for alternative closure options and measures to prevent bleeding.